COMPARISON STUDY OF JOINING Ni-ALLOY WITH GRAPHITE - Abdullah, Awfa Abdul-Rassol (Al-Nahrain Journal of Science, 2010)
Modeling of diffusion bonding of Inconel 600 /Pyrolytic Graphite and Inconel 600/steelinterlayer/Pyrolytic Graphite is investigated in this research. Modeling implies utilization ofANSYS package to predict axisymmetric thermoelastic finite element analysis from the abovematerials. The model is used; to calculate thermal stresses induced across diffusion bonded joints.Investigating thermal stress levels along the potential failure interface for both joints is extremelyhelpful; these residual stresses are mostly the forces of joint failure for both joints. Axisymmetricfinite element analysis involves applying temperature along the whole joint as main parameter; thesecond parameter was changing the steel interlayer.